Syntactic Choices in Indonesian Research Articles from the Disciplines of History Education and Law: What do Authors Prefer? - Warsidi (Didaktika: Jurnal Kependidikan, 2023)
Syntactic studies within both spoken and written texts have been widely conducted. However, studies on this area within research articles are still receiving minor attention from academic scholars. Based on this limited attention, the present study intends to investigate syntactic choices within research articles from the disciplines of History Education and Law in Indonesian journals that receive the Science and Technology Index (SINTA 2). The reason for choosing these selected disciplines is that they have not been investigated to date. For the analysis, a syntactic framework from earlier studies was employed to identify whether research article authors employ simple, compound, complex, and compound-complex sentences. The results revealed that most authors from these two data sets tend to use simple sentences in all sections of research articles. The reason for this finding is discussed in the Finding and Discussion section of this paper. Keywords: Research articles, syntactic choices, the History Education and Law disciplines